Cube Arithmetic: Improving Euler Method for Ordinary Differential Equation using Cube Mean - Nooraida Samsudin; Nurhafizah Moziyana Mohd Yusop; Syahrul Fahmy; Anis Shahida Niza binti Mokhtar (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
The Euler method is a first-order numerical procedure for solving Ordinary Differential Equation (ODEs) problems. It is an effective and easy method to solve initial value problems. Although Euler provides simple procedure for solving ODEs, there have been issues such as complexity, time of processing and accuracy that compelled the use of other, more complex, methods. Improvements to the Euler method have attracted much attention resulting in numerous modified Euler methods. This paper proposes Cube Arithmetic, a modified Euler method with improved accuracy. The efficiency of Cube Arithmetic was compared with Euler Arithmetic and tested using SCILAB against exact solutions. Results indicate that not only Cube Arithmetic provided solutions that are similar to exact solutions at small step size, but also at higher step size, hence producing more accurate results.